Cubic nano-copper(I) oxides as reusable catalyst in consecutive decarboxylative CH arylation and carbonylation: rapid synthesis of carbonyl dibenzofurans. Issue 45 (9th November 2016) - Pal, Rammyani; Chatterjee, Nivedita; Roy, Manas; Sarkar, Sabyasachi; Sarkar, Swarbhanu; Sen, Asish Kumar
Graphical abstract: Highlights: The unique one-step synthesis of carbonyl dibenzofurans was developed. It involves decarboxylative CH arylation and carbonylative CC coupling. The reaction is highly chemo- and regio-selective and environment friendly. Reusable nanodomain cuprous oxide was used as catalyst under aerobic condition. Several derivatives were synthesized which showed high functional group tolerance. Abstract: Consecutive chemo- and regio-selective decarboxylative CH arylation, followed by carbonylative CC coupling of aryl halide with isocyanide/alcohol was applied for the first time in one-step synthesis of carbonyl dibenzofurans with nanodomain cuprous oxide under aerobic condition. As a proof of concept, several novel dibenzofurans were synthesized from 2-(3-iodophenoxy)benzoic acid in good yield. The tandem protocol eliminates the use of excess catalysts, hazardous organic solvents, heavy metals like palladium or rhodium, ligands, oxidants, or external additives. More importantly, the cubic Cu(I) nanocatalyst can be recovered and recycled for three consecutive reactions without any significant loss of catalytic activity or any change in its morphology. Use of water as solvent and reusable catalyst makes the reaction environment friendly.